2016
DOI: 10.1038/mtna.2016.52
|View full text |Cite
|
Sign up to set email alerts
|

Reactivating Fetal Hemoglobin Expression in Human Adult Erythroblasts Through BCL11A Knockdown Using Targeted Endonucleases

Abstract: We examined the efficiency, specificity, and mutational signatures of zinc finger nucleases (ZFNs), transcriptional activator-like effector nucleases (TALENs), and clustered regularly interspaced short palindromic repeat (CRISPR)/Cas9 systems designed to target the gene encoding the transcriptional repressor BCL11A, in human K562 cells and human CD34+ progenitor cells. ZFNs and TALENs were delivered as in vitro transcribed mRNA through electroporation; CRISPR/Cas9 was codelivered by Cas9 mRNA with plasmid-enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 46 publications
0
40
1
Order By: Relevance
“…Because exon 2 is shared by all BCL11A isoforms, frameshift mutations in this region should completely inactivate BCL11A expression from the edited alleles. Although Bjurstrom and colleagues 46 show that BCL11A exon 2-edited mobilized PB-CD34 + can successfully engraft NSG mice, we found the engraftment by edited BM-CD34 + cells to be severely impaired (Figure 6). Because it has recently been reported that BCL11A not only is important for lymphoid development, 49 but also plays a critical role in maintaining vital HSC functions,22, 35, 36 a defect in the engraftment of exon 2 KO/KO cells was therefore not unexpected.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Because exon 2 is shared by all BCL11A isoforms, frameshift mutations in this region should completely inactivate BCL11A expression from the edited alleles. Although Bjurstrom and colleagues 46 show that BCL11A exon 2-edited mobilized PB-CD34 + can successfully engraft NSG mice, we found the engraftment by edited BM-CD34 + cells to be severely impaired (Figure 6). Because it has recently been reported that BCL11A not only is important for lymphoid development, 49 but also plays a critical role in maintaining vital HSC functions,22, 35, 36 a defect in the engraftment of exon 2 KO/KO cells was therefore not unexpected.…”
Section: Discussioncontrasting
confidence: 61%
“…In this study, we used the ZFN genome-editing technology to target BCL11A in primary human BM-derived CD34 + cells instead of mobilized PB-derived CD34 + cells 46 because of the potentially life-threatening complications when mobilizing SCD patients with granulocyte colony-stimulating factor (G-CSF) 47 . BCL11A is a key suppressor of fetal globin expression,17, 18, 20, 48 and the conditional knockout of BCL11A in the erythroid lineage significantly increases fetal globin expression and cured a mouse model of SCD 30 .…”
Section: Discussionmentioning
confidence: 99%
“…While they observed induction of HbF in vitro , the frequencies were likely too low after engraftment in NSG (4%) to be of therapeutic benefit and on top of that, plasmid delivery of the Cas9/sgRNA system resulted in very high toxicities, highlighting the importance of nuclease delivery via RNPs as discussed earlier 27 . Because BCL11A is essential for lymphoid development and may be a risky therapeutic target 28 , Tan et al ., compared genome editing of BCL11A exon 2 and the GATAA enhancer motif.…”
Section: Nhej-based Therapeutic Genome Editing Strategies To Reactivamentioning
confidence: 95%
“…High levels of gene disruption may be achieved in hematopoietic stem and progenitor cells because this type of editing does not require a donor template and can be done via the NHEJ pathway. For example, disruption of the BCL11A erythroid enhancer (a repressor of fetal globin expression) can increase levels of fetal hemoglobin for the treatment of sickle cell disease and beta-thalassemia (Bauer et al, 2013; Bjurström et al, 2016; Canver et al, 2015; Chang et al, 2017). Alternatively, knockout of the CCR5 gene in cells from HIV-infected individuals can prevent ongoing infection by the virus (Cradick et al, 2013; Hendel et al, 2015; Holt et al, 2010; L.…”
Section: Gene Editing Strategiesmentioning
confidence: 99%